2016
DOI: 10.1007/s00421-016-3503-y
|View full text |Cite
|
Sign up to set email alerts
|

An acute session of roller massage prolongs voluntary torque development and diminishes evoked pain

Abstract: Data suggest that RM-induced neural inhibition decreased MVIC F200 and nullified the testing-induced increase in evoked pain associated with 70% tetanic stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 34 publications
5
78
1
8
Order By: Relevance
“…Investigating the influence of rolling massage on maximal force output was not the main purpose of the present study, as our previous experiments had demonstrated that the technique did not alter the maximal force generating capacity (Sullivan et al 2013;Halperin et al 2014;Cavanaugh et al 2017). In line with our previous findings, the MVC force output did not show any significant change following ROLLING.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Investigating the influence of rolling massage on maximal force output was not the main purpose of the present study, as our previous experiments had demonstrated that the technique did not alter the maximal force generating capacity (Sullivan et al 2013;Halperin et al 2014;Cavanaugh et al 2017). In line with our previous findings, the MVC force output did not show any significant change following ROLLING.…”
Section: Discussionsupporting
confidence: 84%
“…Self myofascial release (SMFR) technique using foam roller and roller massager is used extensively in rehabilitation and athletic settings to promote soft-tissue extensibility and enhance recovery from training (for review, see Beardsley and Škarabot, 2015). Previous studies suggest that this technique may enhance range of motion (MacDonald et al 2013;Sullivan et al 2013;Halperin et al 2014;Bradbury-Squire et al 2015;Behara and Jacobson 2017), pressure pain threshold (Pearcey et al 2015;Aboodarda et al 2015;Cavanaugh et al 2017) and arterial dilation and vascular plasticity (Okamoto et al 2014). A "neurophysiological model" has been proposed to explain the influence of SMFR on the musculoskeletal functions.…”
Section: Introductionmentioning
confidence: 99%
“…For the neurophysiological effect, the direct roller compression may influence tissue relaxation and pain in the local and surrounding tissues. For tissue relaxation, the roller compression may induce greater myofascial relaxation or "stretch tolerance" through CNS afferent input from the Golgi tendon reflex and mechanoreceptors (Cavanaugh et al, 2017;Kelly and Beardsley, 2016;Monteiro et al, 2017). For pain, researchers have postulated that roller compression may modulate pain through stimulation of cutaneous receptors (e.g.…”
Section: Mb1 Ball Versus Mbx Ball (Video)mentioning
confidence: 99%
“…For pain, researchers have postulated that roller compression may modulate pain through stimulation of cutaneous receptors (e.g. C-tactile fibers) (Aboodarda et al, 2015), mechanoreceptors (Young et al, 2018), afferent central nociceptive pathways (gate theory of pain) (Cavanaugh et al, 2017), and descending anti-nociceptive pathways (diffuse noxious inhibitory control) (Aboodarda et al, 2015). These postulated responses are often seen clinically by posttest changes in joint ROM and pain perception which lends evidence to the sensitivity of the myofascia to external forces (Grabow et al, 2018).…”
Section: Mb1 Ball Versus Mbx Ball (Video)mentioning
confidence: 99%
“…Recent work suggests that foam rolling can also have nonlocal effects potentially influencing muscle mechanical sensitivity. For example, high-intensity foam rolling or rolling massage may decrease the contralateral or nonlocal muscle mechanical sensitivity (Aboodarda et al 2015;Cavanaugh et al 2017b;Cheatham & Baker 2017;, thereby leading to an enhancement of the stretch tolerance of these muscles. Recent work from Behm's group (Aboodarda et al 2018;Cavanaugh et al 2017a;Young et al 2018) showed that the intervention of foam rolling or rolling massage could even cause the reduction of excitability at the muscular, spinal, and supraspinal levels.…”
Section: Introductionmentioning
confidence: 99%